E-LEARNING SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI INFORMASI - Mohammad Yazdi (Foristek, 2012)
The development of science and technology, especially information technology, internet use in education continues to grow. Use of the Internet is not just for distance education, but also developed in the conventional education system. E-learning is a learning model that is created in digital format through an electronic device. Purpose of the use of elearning in the learning system is to expand access to education public, so that learning modules can be accessed easily, without diabatasi space and time, interactive, and effective. In this paper a prototype using a software development methodology that emphasizes the approach to aspects of design, functionality and user-interface. The final product is expected to be a module-based learning application of information technology.